VALIDITY AND RELIABILITY TEST ON NON-TEST INSTRUMENTS OF LEARNING MOTIVATION OF GRADE IV STUDENTS - Tadzkia, Syifa (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2023)
Learning motivation is an encouragement that can influence students to make changes in behavior in achieving learning goals. The purpose of this research is to describe the results of measuring student motivation obtained through a non-test instrument in the form of a questionnaire. The subjects of this study were fourth grade students at SDN Batok Bali and SDN Leuwiranji 01. The research method used in this article was a sequential exploratory research design (mixed research) with qualitative research, followed by quantitative research. The qualitative method uses literature studies to find additional sources of information from various media. While the quantitative method collects data through measurement using objective and standardized tools, such as SPSS used in this article to test validity and reliability. Instrument requirements that can be said to be valid if the KMO value is > 0,5 and significant < 0,05. After the third test, the anti-image part has no value < 0,5. So of the 20 items in the student learning motivation questionnaire, 14 items are said to be valid. While the reliability requirements are using Cronbach's Alpha, that is, when the value is > 0,7.